2022
DOI: 10.1093/cid/ciac398
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease 2019 (COVID-19) Vaccine Prioritization in Low- and Middle-Income Countries May Justifiably Depart From High-Income Countries’ Age Priorities

Abstract: In high-income countries that were first to roll out coronavirus disease 2019 (COVID-19) vaccines, older adults have thus far usually been prioritized for these vaccines over younger adults. Age-based priority primarily resulted from interpreting evidence available at the time, which indicated that vaccinating the elderly first would minimize COVID-19 deaths and hospitalizations. The World Health Organization counsels a similar approach for all countries. This paper argues that some low- and middle-income coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Therefore, priority-based vaccine allocation is considered a means to effectively distribute vaccine doses based on priority in recourse-constrained LMICs. For instance, age-based priority under the assumption that prioritizing the administration of the vaccine for elderly people may minimize COVID-19 associated deaths and hospitalizations [ 29 ]. Similar approaches are advocated by WHO [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, priority-based vaccine allocation is considered a means to effectively distribute vaccine doses based on priority in recourse-constrained LMICs. For instance, age-based priority under the assumption that prioritizing the administration of the vaccine for elderly people may minimize COVID-19 associated deaths and hospitalizations [ 29 ]. Similar approaches are advocated by WHO [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since our study focuses on diabetic patients, it's conceivable that a higher proportion of individuals in the 41-60 age group had pre-existing diabetes, putting them at greater risk of mucormycosis. This is evident from studies that have explored the impact of COVID-19 vaccination on reducing infection rates in older populations, such as the research conducted by Eyal N et al [ 11 ] and Sezen YI et al [ 12 ]. Regarding gender disparities, our study identified a significant difference in the distribution of mucormycosis cases compared to the research conducted by Rahul Kulkarni et al [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge that our fairness framework takes a Western-centric perspective, particularly with respect to race, and is relevant mostly to countries containing urban areas with high diversity, as is more typical of the global West. The most effective strategy for each country, however, will not be the same (Eyal et al 2022). We therefore propose IM-I to counteract this bias; many non-Western countries may not have the same extent of racial diversity, but will still experience income disparities in their urban areas.…”
Section: Im With Equal Treatmentmentioning
confidence: 99%